Pengaruh Grit Terhadap Perilaku Prokrastinasi Akademik Pada Peserta Didik SMP N 8 Pati - Nika Septyani; Agus Setiawan; Desi Maulia (Universitas Mathla'ul Anwar Banten, 2026)
This research is motivated by academic procrastination behavior in junior high school students. Academic procrastination is the habit of junior high school students postponing school assignments. This behavior can hinder the achievement of learning goals and reduce academic performance. One factor that can influence this behavior is grit, namely a student's perseverance and enthusiasm in achieving long-term goals. Students with high grit tend to be more diligent, persistent, and able to complete assignments on time, while students with low grit are more likely to procrastinate.This research employed a quantitative approach. The population consisted of 242 students, with a sample of 192 students drawn using cluster random sampling. Data were collected using the grit and academic procrastination scales. Data analysis was performed using simple linear regression using SPSS 21. The results of the regression analysis showed a regression coefficient of -0.225 with a significance value of 0.016 (<0.05). This indicates that grit has a negative and significant effect on academic procrastination. This means that every increase in grit will be followed by a decrease in academic procrastination behavior in students. Thus, it can be concluded that grit has an influence on academic procrastination, where the higher the grit possessed by students, the lower the level of academic procrastination.